K2MnGe3S8: a new multifunctional semiconductor featuring [MnGe3S8]2− layers and demonstrating interesting nonlinear optical response and antiferromagnetic properties. Issue 37 (6th September 2018) - Li, Zhuang; Jiang, Xingxing; Yi, Changjiang; Zhou, Molin; Guo, Yangwu; Luo, Xiaoyu; Lin, Zheshuai; Wu, Yicheng; Shi, Youguo; Yao, Jiyong
Abstract : The interplay between NLO-active structural units and transition metals has led to the discovery of a new layered multifunctional chalcogenide, K2 MnGe3 S8 . Abstract : A new multifunctional quaternary chalcogenide K2 MnGe3 S8 was discovered for the first time by using a conventional high-temperature solid-state reaction method. K2 MnGe3 S8 crystallizes in the space group P 21 (no. 4) of the monoclinic system and features a 2∞[MnGe3 S8 ] 2− layer constructed by 1∞[MnGeS6 ] 6− anionic chains and [Ge2 S6 ] 4− dimers. This air-stable compound exhibits a large band gap (about 2.95 eV) and a moderate nonlinear optical (NLO) response (about 0.6 × AgGaS2 with a particle size of 20–41 μm at a laser radiation of 2.09 mm). Moreover, despite the large Mn⋯Mn separation, namely, 7.1978 Å for the shortest intralayer Mn⋯Mn and 6.6975 Å for the neighboring interlayer Mn⋯Mn, K2 MnGe3 S8 exhibits an interesting antiferromagnetic transition at ∼8.1 K. The optical and magnetic properties are also investigated by first principles calculations. Our study demonstrates that the interplay between NLO-active structural units and transition metals may contribute to the discovery of new multifunctional materials.